Financing a Just Transition. (March 2019) - Zadek, Simon
Climate goals can only be realized with a major shift in financing toward low-carbon, climate-resilient assets, notably infrastructure. Progress has been made, but the world is not currently on a viable let alone a just transition pathway. The rules and norms governing the financial system itself are an important factor shaping financial flows. Positively, recent developments highlight a growing receptivity on the part of financial market actors and those governing the financial system to take account of climate and broader sustainable development considerations. Building on such receptivity to reinforce the underlying broader purpose the financial system is a precondition for a just transition.